Hubungan Kinerja Karyawan Terhadap Kepuasan Konsumen Pada Perusahaan PDAM Tirta Betuah Cabang Sembawa - Yunita Hasrina (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2019)
This study aims to identify and analyze Relationship of Employee Performance to Consumer Satisfaction in the Tirta Betuah PDAM Sembawa Branch Company. The variables used in this study is the employee performance and consumer satisfaction.The analytic technique used in this research is simple regression analysis, in this research found that r = 0.0254 which means the relationship between employee work performance and customer satisfaction is very low, based on the results of hypothesis testing shows that there is no relationship between employee work performance with customer satisfaction as indicated by the value a = 0.05 <of the value of t arithmetic / P-Value (0.904) means that H0 is received which indicates that employee performance has no relationship to customer satisfaction